Correlation and Regression studies in induced mutants of chickpea (Cicer arietinum L.) variety Gab (4) - خوري, بولص; رجب , مازن; جبيلي , عبير (Latakia University Journal -Biological Sciences Series, 2020)
Chickpea variety Gab 4 seeds were irradiated by three doses of gamma ray (15, 20, 25) KR, the seeds planted throw season 2017-2018 at the Agricutural Scientific Research Center in Lattakia, to obtain mutants which may compose a base of new varieties in increasing and improving the production activity in future. The correlation relationships between the seed yield and the plant traits in the resulting mutations were studied in order to determine the traits that can be adopted as selection criteria for improving chickpea in the first mutant generation, the strongest desirable and significant correlation of the seed weight was with the number of pods on the plant (r = 0.991 ) at the dose 20KR and (r = 0.969) at the dose of 25KR and (r = 0.867) at the dose of 15KR, while the second strongest correlation to seed weight was with the number of seeds on the plant (r = 0.985), (r = 0.967), and (r = 0.934) at doses 20KR, 25KR and 15KR, respectively. Whereas, the third strongest correlation was with the seed weight trait with the plant height (r = 0.779), (r = 0.519) and (r = 0.488) at doses 20KR, 25KR and 15KR, respectively. Reading the simple regression line equation supported this correlations, so that each increase by one pode on the plant is expected to increase the seed weight of 0.4g seeds / plant with 98% contribution at the dose of 20KR, and 0.5g seeds / plant by 94% contribution at 25KR dose and 0.5g seeds / plant at 15KR dose. It is also expected that increasing one seed in the number of seeds / plant will lead to an increase in the seed weight of 0.3g with a contribution rate of 93%, 0.4 g with contribution of 87%, and 0.4g with a contribution of 87% at doses 20KR, 25KR and 15KR, respectively. Likewise, every 1cm increase in plant height is expected to lead to an increase of about 0.7g seeds / plant, with a contribution 61%, 0.4g seeds / plant with contribution of 27%, 0.4g seeds / plant and 24% contribution at doses 20KR, 25KR, 15KR respectively.